Doing business in a deals world - Kar, Sabyasachi,Pritchett, Lant,Roy, Spandan,Sen, Kunal (United Nations University World Institute for Development Economics Research, 2019)
The World Bank’s Doing Business reports have evoked an intense policy debate about whether countries should simplify regulatory rules in order to stimulate investment and growth, or make them more stringent in order to achieve public policy objectives. Both sides of this debate, however, assume that the business environment in developing countries is defined and determined by the exact implementation of these rules by the state and by firms – an assumption demonstrated to be false by a number of studies. These studies seem to indicate that, rather than these rules, doing business in developing countries is based on deals struck between firms and the political or bureaucratic arms of the state. In this paper, we undertake a cross-country analysis of the relationship between the rules related to doing business and these deals, particularly in the context of the state's capability in implementing them. Using data from the Doing Business reports, the World Bank’s Enterprise Survey and other sources, we show that (i) while there is a relationship between rules and deals, it is a weak one; and (ii) this relationship is itself dependent on the level of a country’s state capability, with the impact of rules on deals getting further weakened if the state capability is low; and (iii) with stringent rules and very low levels of state capability, the relationship becomes perverse, with more stringent rules leading to less compliance, rather than more. Based on these results, we provide a diagnostic approach to rules reform, where the appropriate reform depends on the level of stringency of the rules in a country, and the level of its state capability.
10.35188/UNU-WIDER/2019/715-6
Keywords: Graue Literatur; Doing Business; deals; rules; state capability; investment climate